Implementasi Permenkumham No 9 Tahun 2017 dalam Upaya Memberikan Perlindungan Hukum Jabatan Notaris terhadap Pelaporan TKM - Nisa Nur Ramadhani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is about the implementation of Minister of Law and Human Rights Regulation No. 9 of 2017 in an effort to protect the position of notaries regarding TKM reporting. Reporting Suspicious Financial Transactions (TKM) is a new task that must be carried out by Notaries in accordance with the issuance of Permenkumham No. 9 of 2017 and the inclusion of Notaries as reporting parties in PP No. 43 of 2015. This Permenkumham was issued to support government programs in terms of preventing money laundering crimes. . This type of research is normative juridical with a statutory approach as well as an analytical approach. This research explains, However, this regulation does not explain further about what protections Notaries receive after reporting suspicious financial transactions themselves, as well as the obstacles experienced by Notaries in implementing Permenkumham No. 9 of 2017 in terms of reporting TKM.